CURRICULUM EVALUATION MODELS: A LITERATURE REVIEW - Lisa Apriliana (Jurnal Ilmiah Spectral, 2026)
Curriculum evaluation serves as an essential instrument for determining the degree to which educational programs fulfill their intended purposes in terms of relevance, effectiveness, and overall quality. However, selecting an appropriate evaluation framework remains a persistent challenge, given the wide variety of available models and the differing contextual demands across educational settings. This study aims to analyze and compare the strengths and weaknesses of three widely recognized curriculum evaluation models Tyler's Objective-Centered Model, the CIPP (Context, Input, Process, Product) Model, and Kirkpatrick's Four-Level Evaluation Model through a library research methodology drawing upon peer-reviewed scholarly literature. The analysis reveals that Tyler's model, while offering a clear, sequential logical structure, encounters difficulties when program objectives change and lacks sensitivity to broader contextual factors. The CIPP model presents a thorough, decision-driven evaluation framework applicable to both formative and summative purposes, although its comprehensiveness requires considerable investment of time and resources. Kirkpatrick's model, predominantly applied in training and professional development contexts, provides a practical hierarchical evaluation approach, yet has been criticized for its assumptions about causality and its limited applicability in higher education settings. The study concludes that no single model is universally superior; rather, the selection of an evaluation framework must be informed by the specific objectives, contextual conditions, and intended audience of the curriculum under review.